Pengembangan Kurikulum Raudhatul Athfal Berbasis Kearifan Lokal di RA Selabaya Purbalingga - Mayasari, Novi; Maspupah, Ulpah; Safingah, Kuni (Institute of Research and Public Service Universitas Jenderal Soedirman, 2024)
In an effort to preserve local wisdom and construct knowledge about local wisdom in students from an early age, early childhood education institutions need to implement a curriculum according to local wisdom. This research was a qualitative study. The techniques for the data collection included interviews, observation, and documentation. The yields of this study revealed that the development of the RA Curriculum, according to local wisdom at RA Selabaya Purbalingga, comprised four steps. The first step was to determine the curriculum objectives based on the vision and mission. The second step was to determine learning experiences related to local wisdom. The third step is organizing learning experiences through intracurricular, co-curricular, and extracurricular activities based on local wisdom. The fourth step is to determine a curriculum evaluation based on local wisdom.